STRUKTUR KEPEMILIKAN PADA PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA - Endiana, I Dewa Made (Universitas Muhammadiyah Magelang, 2018)
The performance achieved by the company is very important to assess because itrelates to the prospects and sustainability of the company in the future. Achievingmaximum performance is strongly influenced by several factors, one of which isCorporate Social Responsibility (CSR). This study aims to determine the effect ofownership structure on corporate social responsibility on financial performance of miningcompanies in the Indonesia Stock Exchange for the period 2013-2017. Population is amining company on the Indonesia Stock Exchange. The sample technique was selectedusing purposive sampling, namely the method of determining the sample with certaincriteria so that the number of samples obtained was 11 companies, so the number ofobservations with a study period of 5 years was 55 observations. The results obtained inthis study that corporate social responsibility have a positive effect on performance whilethe ownership structure is not able to strengthen or weaken the relationship of corporatesocial responsibility to the financial performance (ROA) of mining companies listed onthe Indonesia Stock Exchange.